PENGARUH SELF EFFICACY TERHADAP MOTIVASI BELAJAR PESERTA DIDIK BERAGAMA BUDDHA - Agustina, Cindi; Mujiyanto, Mujiyanto; Sukisno, Sukisno (Dharmas Education Journal (DE_Journal), 2024)
This study discusses the impact of self-efficacy on learning motivation. This research aims to find out how much influence self-efficacy has on the learning motivation of Buddhist students at SMPS Pelopor Mandau in 2023/2024. The research design applied in this study is descriptive quantitative, and data was collected using a structured questionnaire method. Data was taken from Buddhist students, who constituted 89 respondents. The correlation value of the self-efficacy variable with learning motivation is 0.702. These results indicate that the relationship between the two variables tested is classified as strong. The conclusion of this research shows that self-efficacy makes a significant contribution to learning motivation, with an influence percentage reaching 49.3%.